2014
DOI: 10.1371/journal.pone.0091186
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination and Degradation of Ribonucleotide Reductase M1 by the Polycomb Group Proteins RNF2 and Bmi1 and Cellular Response to Gemcitabine

Abstract: Ribonucleotide reductase M1 (RRM1) is required for mammalian deoxyribonucleotide (dNTP) metabolism. It is the primary target of the antimetabolite drug gemcitabine, which is among the most efficacious and most widely used cancer therapeutics. Gemcitabine directly binds to RRM1 and irreversibly inactivates ribonucleotide reductase. Intra-tumoral RRM1 levels are predictive of gemcitabine’s therapeutic efficacy. The mechanisms that regulate intracellular RRM1 levels are largely unknown. Here, we identified the E3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 32 publications
2
11
1
Order By: Relevance
“…In accordance with previous published data, we confirmed that a correlation exists between RRM1 levels and resistance to gemcitabine (40,44). Gemcitabine-induced apoptosis was increased and proliferation reduced upon depletion of RRM1 with specific siRNA, confirming its key role in gemcitabine resistance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with previous published data, we confirmed that a correlation exists between RRM1 levels and resistance to gemcitabine (40,44). Gemcitabine-induced apoptosis was increased and proliferation reduced upon depletion of RRM1 with specific siRNA, confirming its key role in gemcitabine resistance.…”
Section: Discussionsupporting
confidence: 92%
“…Downregulation of RRM1 protein did not occur in response to an EGFR inhibitor (gefitinib) but was observed in MEK1/2 knocked down cells, indicating that this effect is specifically dependent on MEK inhibition. A recent study has shown that RRM1 is polyubiquitinated and identified RNF2 and Bmi1 E3 ubiquitin ligases to be involved in RRM1 degradation by the proteasome (44). Our study showed enhancement of RRM1 polyubiquitination through Lys-48-mediated linkage upon pimasertib treatment.…”
Section: Discussionsupporting
confidence: 64%
“…5A). In addition, we observed no clear differential pattern in RRM1 expression upon treatment, most likely due to the induction of ubiquitination and degradation of RRM1 upon gemcitabine treatment (31). However, expression of RRM2 was significantly more upregulated upon gemcitabine and hydroxyurea treatment in BAP1 mut/del compared with BAP1 WT group.…”
Section: Aacrjournalsorgcontrasting
confidence: 58%
“…Gemcitabine directly binds to RRM1 and irreversibly inactivates ribonucleotide reductase [2028]. High RRM1 levels are associated with tumor resistance and low RRM1 levels with tumor sensitivity to gemcitabine treatment [21,23,2528].…”
Section: Lung Cancer Biologymentioning
confidence: 99%